Variability of fibre quality on Chinese Alashan Left Banner White Cashmere goat. Issue 1 (2nd January 2018) - Pallotti, Stefano; Wang, Jun; Tang, Peirong; Antonini, Marco; Lou, Yujie; Pieramati, Camillo; Valbonesi, Alessandro; Renieri, Carlo
Abstract: The heritability and the phenotypic and genetic correlations of down weight (DW), down fibre diameter (DFD), and coefficient of variation of the down fibre diameter (CVDFD) of Chinese Alashan Left Banner White Cashmere goat were estimated on 1375 one-year-old animals, born in 2009, 2011 and 2013 and bred at the Station for Livestock Improvement of Alashan (Left Banner, Inner Mongolia, P.R. China). For all traits, significant effects were for sex, cohort and sex–cohort interaction ( p < .001). The heritability for DFD and CVDFD was high, 0.41 ± 0.08 and 0.52 ± 0.06, respectively. Heritability for the DW was low (0.12 ± 0.03). Phenotypic correlation calculated by Pearson's coefficient showed that DFD is positively correlated with both CVDFD (0.29 ± 0.07) and DW (0.20 ± 0.05). The phenotypic correlation between CVDFD and DW was negative (−0.11 ± 0.06). The genetic correlations between DW and CVDFD and between DFD and CVDFD were both high and positive (0.63 ± 0.16 and 0.39 ± 0.1, respectively) while the DW showed a negative genetic correlation with DFD (−0.27 ± 0.2). Our results suggest that the selection for reducing DFD and its CVDFD is possible and a genetic progress can be achieved quickly in the Chinese Alashan Left Banner White Cashmere goat.